Recombinant granulocyte colony stimulating factor biosimilars. Quality assessment - Zh. I. Avdeeva; A. A. Soldatov; N. A. Alpatova; M. V. Kiselevsky; S. L. Lysikova; V. P. Bondarev; N. V. Medunitsyn; V. D. Mosyagin; V. A. Merkulov; A. N. Mironov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article describes general principles of evidence-based quality assessment research of a recombinant granulocyte colony stimulating factor preparation (G-CSF) under development as well as a confirmation of its similarity to reference preparation (authorized original preparation). Since the quality of biotech preparations is determined by the manufacturing process, when developing a biosimilar one should focus on the manufacturing process details, starting from the selection of the expression system, the composition of excipients, on to the methods of isolation and purification of recombinant protein. Recombinant protein should be characterized in more details, than the quality parameters of the original preparation, included in the specification of the substance or the preparation. Comparative studies include characterization of the active substance and the assessment of the quality of the finished product. The reference preparation in the development of a biosimilar G-CSF